Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445542
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Human Personality and Robot Acceptance in Human-Robot Interaction

Abstract: Human personality has been identified as a predictor of robot acceptance in the human-robot interaction (HRI) literature. Despite this, the HRI literature has provided mixed support for this assertion. To better understand the relationship between human personality and robot acceptance, this paper conducts a meta-analysis of 26 studies.Results found a positive relationship between human personality and robot acceptance. However, this relationship varied greatly by the specific personality trait along with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Moreover, HRI research showed that the attribution of personality traits like extroversion or dominance to the robot can serve as predictors of their social acceptance (Woods et al, 2005 ; Mileounis et al, 2015 ; Dou et al, 2019 ; Tanevska et al, 2019 ; Mou et al, 2020 ). Based on the similarity-complementary hypothesis, it remains inconclusive whether humans do prefer robots with similar personality characteristics or not (Esterwood et al, 2021 ) and whether the personality preference is task-dependent (Joosse et al, 2013 ).…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Moreover, HRI research showed that the attribution of personality traits like extroversion or dominance to the robot can serve as predictors of their social acceptance (Woods et al, 2005 ; Mileounis et al, 2015 ; Dou et al, 2019 ; Tanevska et al, 2019 ; Mou et al, 2020 ). Based on the similarity-complementary hypothesis, it remains inconclusive whether humans do prefer robots with similar personality characteristics or not (Esterwood et al, 2021 ) and whether the personality preference is task-dependent (Joosse et al, 2013 ).…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…The term "individual differences" includes traits such as demographics and personality (Harrison & Rainer, Jr., 1992;Robert, 2018;Robert et al, 2020). Prior research has examined the impact of individual differences on technology adoptions (Esterwood et al, 2021a;Ma et al, 2021). Using the technology acceptance model, Agarwal and Prasad (1999) found that individual differences influence technology acceptance via their effects on individual beliefs about technology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it cannot be overstated that to understand reactions to AI, including public support for regulating it, we must examine how society at large responds to AI. This means examining regulation of AI at a population level and not just using convenience samples of undergraduate students or online Mechanical Turk samples [20].…”
Section: Literature Reviewmentioning
confidence: 99%